Student teachers’ perceptions about their experiences of teaching practice - Matoti, Sheila N; Odora, Ronald J (South African Journal of Higher Education, 2016)
The purpose of the study was to investigate fourth-year student teachers’ perceptions about their experiences of teaching practice. Although the researchers had targeted all fourth-year students enrolled for the Bachelor of Education (B.Ed) degree, only 48 completed and returned the questionnaires. The sample consisted of 26 (54.2%) male and 22 (45.8%) female students. The majority (62.5%) of the students came from the Natural Sciences programme. The study found that with the exception of their placement in schools, the students were satisfied with their preparedness for the experiential training. They were equally satisfied with their school experience, the evaluation of their lessons, and the feedback they received from the evaluation of their lessons. The aspects of teaching where students showed weaknesses were in the use of teaching aids and the use of different assessment techniques. On the whole, their overall confidence in teaching was high. Implications of the findings are indicated in the study.